KEDUDUKAN KEJAKSAAN DALAM PENEGAKAN HUKUM DI BIDANG PASAR MODAL (STUDI KASUS PT. ASURANSI JIWASRAYA) - Marcelino Valentin (LPPM Universitas Ekasakti Padang, 2023)
Attorney is Indonesia government institution who has a duty which regulated in Indonesia Constitution. In this case the attorney authorized to monitoring the activity in capital or stocks markets. Capital markets is one of the key instrument for Indonesia economical growth which is important, but in the Capital markets activity sometimes there’s a things that can make a negative impact and cause a violation of law like fraudulency, embezzlement, forgery, information disclosure and even corruption and the example in Indonesia is PT. Jiwa Sraya Insurance case. Then Indonesia government formed the institution who has a authority to monitoring and organizing capital markets activity including attorney in that. This things is the reason for a writer to make a research about attorney position in law enforcement on a capital markets activity. About how the problems arise in capital markets case with PT. Jiwa Sraya insurance as an example. This research have a purpose to understanding and analyzing the attorney authority and the regulation for capital markets in Indonesia based on Indonesia Constitution 8 of 1995 about capital markets, Indonesia constitution No 20 of 2001 and No. 19 of 2019 about corruption crime.